Hériter de la maison, diriger la maisonnée. Évolutions d’un processus genré dans l’Italie centrale des XIe-XIIIe siècles - Maxime Fulconis (Genre & Histoire)
This article examines the evolution of women’s inheritance rights in central Italy between the eleventh and the thirteenth centuries, focusing on those relatively rare cases of women who inherited their family’s main house or headed their household. In the eleventh century, such a state of affairs remained possible due to the flexibility of Roman and Lombard law, which continued to influence inheritance practices. From the twelfth century onward, however, they became increasingly marginal as customary laws and communal statutes were adopted, restricting women’s hereditary rights and reinforcing patrilineality. This transformation was not limited to material transmission: it also led to a gradual erasure of women from family memory, notably in onomastics. Through the study of notarial, ecclesiastical, and communal sources, this article highlights how the desire to preserve the patrimonial unity of male lineages profoundly reshaped women’s role in the possession and management of the household, understood both as the primary living space and as a familial and residential unit, as well as in broader family and social dynamics.